CRITICAL HIGHER ORDER THINKING MENURUT FILSAFAT PROGRESIVISME DI KALANGAN MAHASISWA - Maradita, Yolanda; Celine Dian Giroth; Metha Putri Paraswati; Soneta Veronika Saogo; Putrie Beatrix Nelly Amalo (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
In the world of education a student is required to be able to think critically and systematically, by connecting the philosophy of Progressivism in the world of Christian Religious Education which affects the cognitive improvement of students in reasoning something. Therefore, this generation whose technological developments are increasingly sophisticated, students should be prepared to face the challenges of the times to come. With the aim of research so that students in